The Effect of Left Lateral Positioning on Hypotension in Cesarean Section Patients Under Spinal Anesthesia Immediately After Injection - Frengky, Frengky JF; Rahmaya Nova Handayani; Septian Mixrova Sebayang (Java Nursing Journal, 2025)
Background: Hypotension is one of the complications that often occurs in cesarean section patients undergoing spinal anesthesia. One non-pharmacological measure that can be taken to prevent hypotension is to change the patient's position to the left side immediately after the spinal anesthesia injection. Purpose: This study aimed to examine the effect of left lateral positioning on the incidence of hypotension in cesarean section patients at Pusri Palembang Hospital. Methods: A quantitative approach with a pre-experimental one group pretest-posttest design was used. A total of 52 patients were selected using purposive sampling. Data were analyzed using the Wilcoxon Signed Ranks Test. Results: The results showed a statistically significant difference in mean arterial pressure (MAP) before and after the left lateral positioning, with a Z value of -6.283 and a p-value < 0.001. The average MAP increased from 65.81 mmHg to 77.77 mmHg, and the average heart rate decreased from 112.40 bpm to 80.58 bpm. These results indicate that the left lateral position is effective in stabilizing patient hemodynamics and reducing the risk of hypotension. Conclusions: This finding supports the use of left lateral positioning as a simple, non-invasive, and cost-effective initial intervention in obstetric spinal anesthesia management.